Google Apps Script complete course beginner to advanced - Svekis, Laurence (Packt Publishing, 2018)
"This course will take you on a journey where you'll learn to power up your Google Suite products using Apps Script to connect, automate, and add advanced functionality. Apps Script allows you to power up your favorite Google apps and do more with them, way more. Automate, add functionality, use spreadsheet data, create documents, interact with email, generate reports, use data more effectively--the list of amazing things you can do with Google Apps Script is endless. Just like JavaScript, Apps Scripts are easy to write and use the same structure and core fundamental functionality as JavaScript. If you know JavaScript, you can get started with Apps Script in minutes. Functions, variables, loops, and more use the same syntax as JavaScript. With the added power of Google Classes, you can connect data from your Google apps and build on it. It's the easy way to power up your applications."--Resource description page
Title from resource description page (Safari, viewed October 23, 2018)
Keywords: Google Apps; JavaScript (Computer program language); Application software -- Development; Cloud computing; JavaScript (Langage de programmation); Logiciels d'application; Développement; Infonuagique; Application software; Development